Advanced controller design for D-FACTS device in grid-connected photovoltaic system controller - Ali Jaber AlQattan; Fadhel Albasri; Sayed Ali Al-Mosawi (International Journal of Advances in Applied Sciences, 2024)
Photovoltaic (PV) solar energy is considered one of the highest renewable energy (RE) resources worldwide. Hence, PV system installation capacity is increasing, triggering new power quality problems in grid systems. Some examples of these problems include unbalanced voltages, fluctuating power levels, harmonic distortions, or reverse power flow. To mitigate the adverse impacts of PV integration on voltage regulation and harmonic distortion in electrical distribution systems, a distribution static synchronous compensation (D-STATCOM) is considered a solution. A simulation study is performed by modeling a power system model with an integrated PV system and D-STATCOM. Two control schemes, proportional-integral (PI) and artificial neural network (ANN), were applied within the internal control of D-STATCOM to enhance the power quality of the power system. Two different inverter configurations were adapted, a sinusoidal pulse width modulation (SPWM) and a hysteresis current controller (HCC). Results are obtained as voltage profiles for all the considered control schemes with different inverter types under different contingency conditions. The performance is also evaluated by control characteristics evaluation for different controllers. The controller ANN has better performance than the PI controller and it can mitigate power quality problems and the impact of the PV integration on voltage regulation and harmonic distortion.